THU0440 Lupuspro is Responsive to Changes in Disease Activity over Time. (10th June 2014) - Giangreco, D.; Devilliers, H.; Annapureddy, N.; Block, J.A.; Jolly, M.
Abstract : Background: Patient reported outcome (PRO) tools are important to understand, educate, manage, and follow patients with systemic lupus erythematosus (SLE). Disease targeted PRO for SLE (LupusPRO) has good reliability and has been validated in several languages and cultural contexts. LupusPRO could be better integrated into routine clinical care and clinical trials in SLE if it was also found to be responsive to physician assessed changes in disease activity. Objectives: To test the responsiveness of LupusPRO domains to changes in physician disease activity assessments in the routine clinical care setting. Methods: Longitudinal data on LupusPRO and disease activity assessments were collected in the Rush Lupus Data Repository during routine clinical care visits. We tested only the responsiveness of the health related quality of life domains (HRQOL), as we expect these to change over short periods of time in response to the disease, unlike the non-HRQOL domains. Disease activity assessments used as anchors for testing responsiveness included the SLEDAI physician global assessment (PGA), Total SELENA-SLEDAI, and the SELENA-Flare Index (SFI) (Yes/No). Cut-offs used to determine change in disease activity were PGA (change of 0.3), SELENA-SLEDAI (change of 4), and SFI (remitting, stable and flaring). Non-parametric analysis of variance was used to compare changes in LupusPRO HRQOL domains against disease activity anchors. Results: There were 658 visit data available for 185 patients. Consecutive visits were 2-5 months apart. PGA was available for 651 visits; Total SLEDAI was available for 269 visits; SFI was available for 614 visits. Mean (SD) age and SELENA-SLEDAI were 43.5 (13.2) years and 6.4 (7.3), respectively. PGA changed significantly for 281 visit data (increased in 132, decreased in 142), while 377 visit data had unchanged PGA. LupusPRO HRQOL domains that changed significantly in the appropriate direction included Lupus Symptoms (p<0.001), Procreation (p=0.03), Pain-Vitality (p=0.002), Emotional Health (p=0.06), and Body Image (p=0.03). SELENA-SLEDAI changed significantly among 73 visits (32 increased, 41 decreased), and remained stable among 196 visits. LupusPRO HRQOL domains of Lupus symptoms (p=0.0004) and Pain-Vitality (p=0.02) responded significantly and in the appropriate direction. Significant changes in SFI were observed in 151 visit data (79 remitting, 72 flaring), while 463 visit data was unchanged. LupusPRO HRQOL domains that responded significantly in the appropriate direction in response to changes in SFI were Lupus symptoms (p<0.001), Procreation (p 0.005), Physical Health (p=0.0006) and Pain-Vitality (p<0.0001). Mixed model analysis supported similar results. Conclusions: Most HRQOL domains of LupusPRO are responsive to physician-assessed changes in disease activity in the patient care setting in SLE. LupusPRO is an appropriate tool to be used not only in clinical trials but also in the clinical setting. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3238